Financial control with the help of information technologies (Путеводитель предпринимателя, 2020)
The meaning offinancial control is presented in the article, the importance offinancial control for practical activity is described. The role of using information technologies in the organization offinancial control is pointed out. The main requirements for information technologies used as an instrument offinancial control are formulated.